Tyreopatie, dyslipidemie a kardiovaskulární rizika - Jiskra, J; Límanová, Z; Antosová, M (Vnitrni lekarstvi, 2007)
By affecting the metabolism of lipids, hypothyroidism accelerates the process of atherogenesis and increases cardiovascular risk. In manifest hypothyroidism the number of LDL receptors in the liver decreases and there is an increase in levels of overall cholesterol, LDL-cholesterol and apolipoprotein B in the blood. Levels of HDL particles remain normal or even rise slightly as a result of reduced activity of the Cholesterol ester transfer protein (CETP) and hepatic lipase. This leads to a reduction in the transport of cholesterol esters from HDL-(2) to VLDL and IDL. Subclinical hypothyroidism also has a negative effect on the lipid profile, but is more likely to lead to pro-atherogenic changes in the proportion of lipid particles than to a reduction in overall cholesterol. Subclinical hypothyroidism leads to the manifestation of certain risk factors of atherosclerosis. Although studies of overall mortality and cardiovascular morbidity have not been completely unanimous in their conclusions, increased cardiovascular risk can be considered likely in subclinical hypothyroidism. It remains an open question whether the treatment of subclinical hypothyroidism with levothyroxine. At present we have only indirect proof from studies that assessed the effect of levothyroxine treatment on risk factors of atherosclerosis. Starting treatment with lipid lowering agents (especially statins) for (sub)clinical hypothyroidism is extremely risky though due to the risk of the development or worsening of myopathy, which is a further cogent argument for the active screening and treatment of(sub)clinical hypothyroidism for all patients with dyslipidemia.
Keywords: rizikové faktory; ateroskleróza; Cholesterol Esters; estery cholesterolu; Dyslipidemias; kardiovaskulární nemoci; Cardiovascular Diseases; lidé; dyslipidemie; Risk Factors; Atherosclerosis; Hypothyroidism; Humans; metabolismus lipidů; Lipid Metabolism; hypotyreóza